Islamic activism : a social movement theory approach - Wiktorowicz, Quintan, 1970- (Indiana series in Middle East studies., 2004)
" ... [Will] have an impact on two important fields of scholarship: social movement theory and the study of Islamic activist movements."--John Voll, Georgetown UniversityThis volume represents the first comprehensive attempt to incorporate the study of Islamic activism into social movement theory. It argues that the dynamics, processes, and organization of Islamic activism can be understood as important elements of contention that transcend the specificity of "Islam" as a system of meaning and identity a